2017
DOI: 10.1016/j.orgel.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability of naphthyl end-capped oligothiophenes in organic field-effect transistors measured by grazing-incidence X-ray diffraction in operando

Abstract: . (2017) Structural stability of naphthyl end-capped oligothiophenes in organic field-effect transistors measured by grazingincidence X-ray diffraction in operando. Organic Electronics. Permanent WRAP URL:http://wrap.warwick.ac.uk/89989 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
7
21
0
Order By: Relevance
“…The smearing of the Bragg peaks along q z suggests that NaT3 exhibits a higher degree of disorder along the stacking direction perpendicular to the surface normal compared with the closely related but symmetrical 5,5 0 -bis(naphth-2-yl)-2,2 0 -bithiophene (NaT2), which shows equally resolved Bragg peaks (rather than rods) in both directions. 7 Yet the pattern has a prominent similarity to what is reported for 5-decyl-5 00 -(naphthalen-2-yl)-2,2 0 :5 0 ,2 00 -terthiophene (D3TN) in Ref. 23, which likewise contains three thiophene rings with one end-group replaced by an alkyl-group.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The smearing of the Bragg peaks along q z suggests that NaT3 exhibits a higher degree of disorder along the stacking direction perpendicular to the surface normal compared with the closely related but symmetrical 5,5 0 -bis(naphth-2-yl)-2,2 0 -bithiophene (NaT2), which shows equally resolved Bragg peaks (rather than rods) in both directions. 7 Yet the pattern has a prominent similarity to what is reported for 5-decyl-5 00 -(naphthalen-2-yl)-2,2 0 :5 0 ,2 00 -terthiophene (D3TN) in Ref. 23, which likewise contains three thiophene rings with one end-group replaced by an alkyl-group.…”
supporting
confidence: 67%
“…5,6 Of particular interest are thiophene-based oligomers because of their hole transport properties and stable device performance under atmospheric conditions. [7][8][9] By end-capping the thiophene rings with aryl groups, the polymerization potential is hindered and intermolecular packing is promoted. 9 We have recently shown that the photoresponsivity in naphthyl end-capped oligothiophene based OPTs can be enhanced by utilizing the plasmonic properties of embedded metallic nanoparticles.…”
mentioning
confidence: 99%
“…We have recently started to focus on the most symmetric variant of these materials, 5,5´-bis(naphth-2-yl)-2,2´-bithiophene (NaT2, Scheme 1), and investigated the relation between structure and OFET environment, and confirmed the stability hypotheses of Geng and co-workers by X-ray investigations of NAT2 OFETs in operando. 20 At the same time, Balzer et al 21 have found how NaT2 forms an extraordinary fiber-like surface morphology on muscovite mica, presumably originating from the anisotropy of the muscovite surface. These findings make NaT2 an intriguing new candidate when turning to the fundamentals of surface controlled crystal growth.…”
Section: Introductionmentioning
confidence: 98%
“…previously. [13][14][15] NaT2 and NaT3 have many similarities. Phenomenologically, these films exhibit a plate like crystal habit when grown on SiO 2 .…”
Section: Methodsmentioning
confidence: 99%